The complete chloroplast genome sequences of Pistacia chinensis Bunge, a potential bioenergy tree. Issue 1 (2nd January 2019) - Xu, Jiu-Heng; Zhang, Dong-Xu; Sun, Kuo; Wang, Xin-Rui; Xiang, Qiu-Hong; Wang, Qing; Guan, Wen-Bin
Abstract: In this study, the complete chloroplast genome of Pistacia chinensis Bunge, a bioenergy tree whose seed oil has been proposed as a promising feedstock for both edible and industrial oil, was generated. The chloroplast genome of P. chinensis was 160, 618 bp long, which was comprised of a large single copy (LSC) region of 88, 371 bp, a small single copy (SSC) region of 19, 057 bp, and a pair of inverted repeats (IRs) of 26, 595 bp. The chloroplast genome GC content was 37.87%, contained 132 genes, including 87 protein-coding genes, eight rRNA genes, and 37 tRNA genes. Phylogenetic analysis revealed that P. chinensis was closely grouped with P. vera and P. weinmaniifolia, belonging to the Anacardiaceae family.